A Pilot Study of Ultrasonography-Naïve Operators' Ability to Use Tele-Ultrasonography to Assess the Heart and Lung. (July 2020) - Olivieri, Peter P.; Verceles, Avelino C.; Hurley, Julie M.; Zubrow, Marc T.; Jeudy, Jean; McCurdy, Michael T.
Introduction: Remotely tele-mentored ultrasound (RTMUS) involves the real-time guidance of US-naïve providers as they perform point-of-care ultrasound (POCUS) by remotely located, US-proficient providers via telemedicine. The concordance between RTMUS and POCUS in the evaluation of critically ill patients has not been reported. This study sought to evaluate the concordance between RTMUS and POCUS for the cardiopulmonary evaluation of patients in acute respiratory insufficiency and/or shock. Methods: Ultrasound-naÏve nurses performed RTMUS on critically ill patients. Concordance between RTMUS and POCUS (performed by critical care fellows) in the evaluation of the heart and lungs was reported. The test characteristics of RTMUS were calculated using POCUS as a gold standard. Concordance between RTMUS and available transthoracic echocardiography (TTE) and computed tomography (CT) scans was also reported. Results: Twenty patients were enrolled. Concordance between RTMUS and POCUS was good (90%-100%) for left ventricle function, right ventricle (RV) dilatation/dysfunction, pericardial effusion, lung sliding, pulmonary interstitial syndrome, pleural effusion, and fair (80%) for lung consolidation. Concordance between RTMUS and TTE or CT was similar. RTMUS was highly specific (88%-100%) for all abnormalities evaluated and highly sensitive (89%-100%) for most abnormalities although sensitivity for the detection of RV dilatation/dysfunction (33%) and pulmonary interstitial syndrome (71%) was negatively impacted by false negatives. Conclusions: RTMUS may be a reasonable substitute for POCUS in the cardiopulmonary evaluation of patients with acute respiratory insufficiency and/or shock. These findings should be validated on a larger scale.